2014
DOI: 10.4103/0970-4388.130983
|View full text |Cite
|
Sign up to set email alerts
|

Seckel syndrome: A rare case report

Abstract: Seckel syndrome (SS) is a rare, autosomal recessive syndrome; characterized by severe intrauterine and postnatal growth retardation, microcephaly, mental retardation, and typical facial appearance with beaklike protrusion of the midface (bird headed). In addition to the characteristic craniofacial dysmorphism and skeletal defects, abnormalities have been described in the cardiovascular, hematopoietic, endocrine, gastrointestinal, and central nervous systems. Usually such patients have poor psychomotor developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…Another alteration found in children was the cleft lip and palate, with a prevalence of 1.74%. The study conducted by Zen et et al 36 verified the marked presence of cleft palate and / or lip in children with Edwards Syndrome, just as Sisodia et al, 37 found in individuals with Seckel Syndrome.The prevalence of oral candidiasis in this study was 1.74%, considered low when compared to the studies by Yilmaz et al, 38 who cite oral candidiasis as the most prevalent change in their results among other pathologies common to early childhood, with 10.70%. As in the results by Cruz et al, 39 who found a prevalence of 5.45% of pseudomembranous candidiasis, with 8.86% in children aged 3-6 years when compared to other age groups.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Another alteration found in children was the cleft lip and palate, with a prevalence of 1.74%. The study conducted by Zen et et al 36 verified the marked presence of cleft palate and / or lip in children with Edwards Syndrome, just as Sisodia et al, 37 found in individuals with Seckel Syndrome.The prevalence of oral candidiasis in this study was 1.74%, considered low when compared to the studies by Yilmaz et al, 38 who cite oral candidiasis as the most prevalent change in their results among other pathologies common to early childhood, with 10.70%. As in the results by Cruz et al, 39 who found a prevalence of 5.45% of pseudomembranous candidiasis, with 8.86% in children aged 3-6 years when compared to other age groups.…”
Section: Discussioncontrasting
confidence: 79%
“…Gusmão et al, 4 and Silva et al, 5 also verified the presence of opacities and hypoplasia in these children, with a prevalence of 28.10% and 30.76%, respectively.In the case of congenital syndromes, it is observed that hypoplasia is a very common DDE. 37,38 In this study, however, the greatest occurrence of changes in enamel development was represented by hypocalcification, with a prevalence of 20.59%. No alteration of the isolated hypoplasia type was observed, with only 1.47% of hypoplasia associated with hypocalcification.…”
Section: Discussionmentioning
confidence: 48%
“…3 The diagnosis of this syndrome is mainly based on clinical findings. 16 However, pregestational consultation and genetic diagnosis are of particular importance as the next offspring of a family with a known case of Seckel syndrome has a 25% chance of being affected. 17,18 Intrauterine ultrasound features, including abnormal head appearance, extreme microcephaly, cystic hygroma, encephalocele, posterior fossa cysts, cortical dysplasia and corpus callosum agenesis, can also be exploited for prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…MCDs clinical manifestations include epilepsy, autistic features, ID and developmental delay, coupling MCDs with neuropsychiatric disorders. For example, individuals with Rett Syndrome present microcephaly and ASD at the same time, while in Seckel and Angelman syndrome patients exhibit microcephaly and ID ( Sisodia et al, 2014 ). Patients with Prader-Willi ( Bennett et al, 2015 ) and Timothy syndrome ( Bauer et al, 2021 ) suffer from both ID and ASD, while in Fragile X syndrome characteristics of ASD, ID, and ADHD are present simultaneously.…”
Section: Using the Correct System In Modeling Neurodevelopmental Diso...mentioning
confidence: 99%